Soteriologiczne ześrodkowanie w protologii Pierre Teilharda de Chardin - Andrzej Jarosiewicz (Wrocławski Przegląd Teologiczny)
The human is a great mystery to himself and to the world he lives in. The mystery of the human is the reflection of the mystery of God, who – within the structure of the human – has left a trace of the biblical image and the likeness to Himself as the Creator. This perspective sheds light on the great paradox: God – for his love for the human – chose to incarnate his only Son so that in Him the greatest mystery of salvation is brought about. In the light of thus oriented study of the human and the world around him, many theologians and philosophers have sought for the answer to certain questions that bothered them. These questions concern the cause and purposefulness of the creation of humankind, and the methodology of “reading” God’s revelation which expresses what God has done to all of us because of love. One of the answers is put forward by the still valid theological thought of father Pierre Teilhard de Chardin who, in an “unusual” way, reads the divine vision of God and the human.